The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18820/2519593x/pie.v39.i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the wicked problem of feedback during the teaching practicum

Carisma Nel,
Elma Marais

Abstract: COVID-19 affected the teaching practicum placement of approximately 650 fourth year BEd Foundation Phase student teachers at University N in April and July 2020. The teaching practicum is seen as a purposeful, organised, supervised, mentored and assessed educational activity required for the completion of a teacher education programme. During the teaching practicum, the provision of feedback from teacher educators as well as mentor teachers forms an integral part of the learning process and enriches student te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…A range of digital technologies were used and adapted—across synchronous and asynchronous teaching and learning, as well as in assessment (Table 1 ). Some studies focused on particular technologies and adaptations (Nel & Marais, 2021 ), but more commonly research was focused on the overall experiences of adaptation to online learning. The clarity of the level of acceptance and use of specific technologies pre-COVID-19 at each institution was provided in only a few studies, consequently making it challenging to determine the pre- and post-experiential changes in experience in response to adaptation of technology use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A range of digital technologies were used and adapted—across synchronous and asynchronous teaching and learning, as well as in assessment (Table 1 ). Some studies focused on particular technologies and adaptations (Nel & Marais, 2021 ), but more commonly research was focused on the overall experiences of adaptation to online learning. The clarity of the level of acceptance and use of specific technologies pre-COVID-19 at each institution was provided in only a few studies, consequently making it challenging to determine the pre- and post-experiential changes in experience in response to adaptation of technology use.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of use of platforms and applications, the results also showed that enhanced efficiency in handling assignments for staff (Chen et al, 2021 ), as well as increased use of online formative and summative tests were evident (Laher et al, 2021 ). The use of different forms of content and complementary apps was evident through the use of tools such as Net.Create and Perusall (Craig et al, 2020 ; Nel & Marais, 2021 ). However, a proliferation of different apps and lack of consistency between different lecturers and courses created challenges for the student experience (Ghazi-Saidi et al, 2020 ; Oliveira et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the university level, its positive impact on student motivation, engagement, learning and community building has been investigated in subjects including statistics (Nokelainen et al, 2005), second language Spanish courses (Thoms & Poole, 2017), teacher education (Nor et al, 2013), EAL courses (Tseng et al, 2015), second language Chinese courses (Thoms et al, 2017), physics (Miller et al, 2016) and politics (Clarke, 2019). With the pandemic dramatically altering course delivery in the tertiary education sector, researchers have been investigating social annotation tools, such as Perusall, in various fields, including philosophy (Biro, 2021), pre‐service teacher education (Nel & Marais, 2021) and engineering (d'Entremont & Eyking, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…2 The forced changes brought about due to the pandemic and the digital shift have allowed many teacher educators to rethink one of the "wicked problems" of the work-integrated learning (WIL) (i.e., the teaching practicum) component of preservice teachers' education, namely feedback. 3 Feedback during WIL is considered to be a risky, uncertain and inconsistent endeavour. 4 Student teachers express dissatisfaction and frustration about the timeliness of the feedback, the inability to act on the feedback, the lack of explanation of the use of rubrics and sometimes the incomprehensibility.…”
Section: Introductionmentioning
confidence: 99%